Impact of a homestead food production program on women's empowerment: Pro-WEAI results from the FAARM trial in Bangladesh. (October 2022) - Waid, Jillian L.; Wendt, Amanda S.; Sinharoy, Sheela S.; Kader, Abdul; Gabrysch, Sabine
Highlights: We evaluated women's and men's agency in agriculture in an RCT in rural Bangladesh. The intervention supported gardening and poultry rearing through farmer groups. We used the project-level Women's Empowerment in Agriculture Index, a new method. Intervention women had greater intrinsic and collective, but not instrumental, agency. The intervention resulted in higher self-efficacy among both women and men. Abstract: Nutrition-sensitive agricultural programs have the potential to improve women's and children's nutrition, along with women's empowerment. The project-level Women's Empowerment in Agriculture Index (pro-WEAI) aims to standardize the measurement of women's agency and enable the assessment of impact over typical project timelines. Within the Food and Agricultural Approaches to Reducing Malnutrition (FAARM) cluster-randomized controlled trial in rural Habiganj, Sylhet, Bangladesh, we examined quantitative pro-WEAI data collected from a subsample of trial participants and their husbands (n = 885) approximately four months after the end of the intervention. We evaluated the impact of a three-year homestead food production program on men's and women's agency separately by pro-WEAI domain and indicator, using multilevel logistic and linear regression. We show that women in the FAARM intervention group had levels of agency similar to men and much higher than women in the control group (Odds Ratio [OR] 7.7, p < 0.001), corresponding to better gender equity in intervention areas (OR 3.5, p < 0.001). The higher levels of agency among intervention women were driven by greater intrinsic and collective agency but not by instrumental agency. Compared to controls, more women in the intervention group found intimate partner violence unacceptable (OR 3.5, p < 0.001), had greater ownership of assets (OR 2.6, p = 0.001), better control of income (OR 1.8, p = 0.042), higher levels of group membership (OR 14.0, p < 0.001), and membership in groups they considered influential (OR 166.8, p < 0.001). Self-efficacy was greater in intervention areas for both women (OR 3.2, p < 0.001) and men (OR 2.3, p = 0.002). Our results contribute to the development of benchmarks for interpreting pro-WEAI scores across programs. Our assessment of the impact of a homestead food production program on women's agency provides additional rationale for women-led agricultural projects. We plan to build on these findings by examining the role of improved women's agency on the pathway from the intervention to nutritional impacts.